Pedagogical Management of Teaching Performance in Basic Education of Educational Institutions in Colombia (CONOCIMIENTO, INVESTIGACIÓN Y EDUCACIÓN CIE, 2024)
The objective of this review article is to analyze the pedagogical management of teaching performance in basic education in Colombia. The research was documentary with bibliographic design. The theoretical development and analysis indicate that the pedagogical management of teaching performance in basic education is fundamental as it constitutes a set of organized and systematic processes of learning strategies with the support of technological tools. It is confirmed that the pedagogical management of teaching performance in basic education must be focused on reflection on the teaching task and student learning, which contributes to improving their performance with quality.
Keywords: pedagogy; educational methods; evaluation; organization and planning; education